Effects of PDE type 5 inhibitors on Left Ventricular Diastolic Dysfunction in Resistant Hypertension - Faria,Ana Paula Cabral de (2015)
Resistant hypertension (RHTN) is a multifactorial disease characterized by blood pressure (BP) levels above goal (140/90 mmHg) in spite of the concurrent use of three or more antihypertensive drugs of different classes. Moreover, it is well known that RHTN subjects have high prevalence of left ventricular diastolic dysfunction (LVDD), which leads to increased risk of heart failure progression. This review gathers data from studies evaluating the effects of phosphodiesterase-5 (PDE-5) inhibitors (administration of acute sildenafil and short-term tadalafil) on diastolic function, biochemical and hemodynamic parameters in patients with RHTN. Acute study with sildenafil treatment found that inhibition of PDE-5 improved hemodynamic parameters and diastolic relaxation. In addition, short-term study with the use of tadalafil demonstrated improvement of LVDD, cGMP and BNP-32 levels, regardless of BP reduction. No endothelial function changes were observed in the studies. The findings of acute and short-term studies revealed potential therapeutic effects of IPDE-5 drugs on LVDD in RHTN patients.